2018
DOI: 10.1177/0193945918809714
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep Quality, Depression Symptoms, and Blood Glucose in Pregnant Women

Abstract: Sleep quality during pregnancy affects maternal/child health. We aimed to assess changes in sleep quality during pregnancy and determine its relationship to maternal mood, blood glucose, and work schedule among primiparous women. We conducted a prospective/longitudinal/observational study. Ninety-two pregnant women were recruited from Midwestern hospital. Mood and sleep quality data were collected using Edinburgh Postnatal Depression Scale/Pittsburgh Sleep Quality Index at Gestational Weeks 22 and 32. Forty-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
(50 reference statements)
4
17
1
1
Order By: Relevance
“…The remaining were withdrawn by research staff due to lack of compliance to study protocol. There was no difference in demographic variables between recruited, retained and withdrawn populations [18,19].…”
Section: Population and Settingmentioning
confidence: 80%
See 3 more Smart Citations
“…The remaining were withdrawn by research staff due to lack of compliance to study protocol. There was no difference in demographic variables between recruited, retained and withdrawn populations [18,19].…”
Section: Population and Settingmentioning
confidence: 80%
“…Across all study time points r24 was significantly related with cortisol amplitude, which suggests that rest-activity behaviors affect the quality of cortisol rhythms. Our previous study of this population, found that women who worked daytime shifts had significantly better self-assessed sleep quality than those who worked eveningnight or rotating shifts [19]. The subset of the population that was unemployed had a wide variability in sleep quality scores, resulting in no difference in sleep quality between group and day-time or shift/night workers.…”
Section: Considerations Of Study Population and Study Limitationsmentioning
confidence: 91%
See 2 more Smart Citations
“…Sleep disruptions are common during pregnancy [1] and are associated with an increased risk of adverse maternal/fetal outcomes such as hyperglycemia [2,3], gestational diabetes [4], preeclampsia [5], cesarean delivery [6], longer labor [7], and delivering a low birthweight infant [8]. Additionally, women with poor sleep in pregnancy experience increased depressive symptoms during pregnancy [9] and postpartum depression [10], which increase their risk of depression later in life [11].…”
Section: Introductionmentioning
confidence: 99%